Keefektifan Model Pembelajaran Tipe CIRC (Cooperative Integrated Reading and Composition) terhadap Minat dan Hasil Belajar pada Materi Akar Pangkat Tiga Bagi Siswa Kelas VI Sekolah Dasar - Suharno Suharno; Rasiman Rasiman; Ida Dwijayanti (Jurnal Kualita Pendidikan, 2022)
One of the goals of learning mathematics is so that students can have skills in solving a problem. In order to increase the positive attitude of students, the material must be designed in such a way, so that it is suitable to achieve the teaching goals that have been determined to be achieved. Therefore, it is necessary to choose a learning model that is estimated to be appropriate to use. One of them is the cooperative learning model that can help students improve positive attitudes including building confidence in their ability to solve math problems. There are many cooperative learning models in mathematics learning that meet the characteristics of effective learning, including the CIRC type cooperative model (Cooperative Integrated Reading and Composition) which can help students hone problem solving skills in solving story problems. So that with this learning model students are able and skilled to solve problems in story problems with the right steps. The purpose of this study was to determine the effectiveness of the CIRC model in improving student learning outcomes and student interest in learning. This research was a research experiment carried out at SD Negeri Sendang and SD Negeri Gondo 01, in grade VI students.